2005
DOI: 10.1213/01.ane.0000143337.05366.cd
|View full text |Cite
|
Sign up to set email alerts
|

Does Methemoglobin from Oxidized Hemoglobin-Based Oxygen Carrier (Hemoglobin Glutamer-200) Interfere with Lactate Measurement (YSI 2700 SELECT??? Biochemistry Analyzer)?

Abstract: In this study, we validated the accuracy of lactate measurements (YSI 2700 SELECT glucose/lactate analyzer) in the presence of methemoglobin from an oxidized bag of hemoglobin-based oxygen carrier (Met-HBOC), hemoglobin glutamer-200 (Oxyglobin; Biopure Corp). Different combinations of concentrated L-lactate solution, pooled canine plasma, and Plasmalyte A were added to 4 sample groups (1%, 10%, 20%, and 40% Met-HBOC [1.3 g/dL]) to yield linear increases in lactate concentration in consecutive samples. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Khan et al (2003) observed insignificant increase in methemoglobin in an opened bag HBOC over the course of one day of research. However, Moallempour et al (2009) and Osgood et al (2005) have reported that prolonged exposure of HBOC to air for months would result in the formation of methemoglobin up to 65–80%. Therefore, we took the following precautions in the handling of HBOC: a) withdrawing HBOC from the storage bag without injecting air into the bag, b) limiting the maximum duration for using a given bag to 1 week, and c) storing HBOC at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al (2003) observed insignificant increase in methemoglobin in an opened bag HBOC over the course of one day of research. However, Moallempour et al (2009) and Osgood et al (2005) have reported that prolonged exposure of HBOC to air for months would result in the formation of methemoglobin up to 65–80%. Therefore, we took the following precautions in the handling of HBOC: a) withdrawing HBOC from the storage bag without injecting air into the bag, b) limiting the maximum duration for using a given bag to 1 week, and c) storing HBOC at 4°C.…”
Section: Methodsmentioning
confidence: 99%